A framework for effective threat hunting. Issue 6 (June 2019) - Bhardwaj, Akashdeep; Goundar, Sam
Abstract : In today's dynamic cyber security environment, with its rapidly changing threat landscape, companies are becoming increasingly aware of the necessity of getting ahead of new cyber attack trends. It is for this reason that threat hunting has become so popular. A new wave of attacks has become exceptionally proficient in successful, undetected intrusions, breaching network defences, exploiting system vulnerabilities and obtaining access to organisations' systems and data.